Simultaneous extraction of crude polysaccharides, soluble proteins, gingerols, and shogaols from dried ginger by subcritical water extraction - Winatta Sakdasri; Sunanta Kaomaneechot; Sarida Lasim; Pichayada Somboon; Natthaporn Chotigavin; Patthranit Wongpromrat; Ruengwit Sawangkeaw (LWT, 2025)
Subcritical water extraction (SWE) is a remarkable method for the simultaneous extraction of high- and low-polarity bioactive compounds from ginger. This study investigated the effects of temperature, pressure, and extraction time on the crude polysaccharide yield, protein content, total phenolic content (TPC), and amounts of 6-gingerol and 6-shogaol. The pressure was maintained at 30 bars, and the temperature and extraction time were optimized to maximize the polysaccharide yield, protein, TPC, gingerols, and shogaols contents. The rising temperatures (100–160 °C) and extended extraction times (10–50 min) enhanced the yield and TPC but negatively affected protein stability, leading to thermal degradation when the temperature surpassed 180 °C. Specifically, the content of 6-gingerol decreased at high temperatures because of its conversion into 6-shogaol. The optimal extraction conditions were 160°C for 40 min at 30 bars, resulting in a polysaccharide yield of 8.54%, protein content of 100.35 mg body surface area/g dry mass, TPC of 18.10 mg Galic acid (GA)/g dry mass, 6-gingerol content of 2.14 mg/g dry mass, and 6-shogaol content of 0.28 mg/g dry mass. Therefore, SWE effectively extracts various polar bioactive compounds from plant materials in a single step. • Subcritical water facilitated co-extraction of high-polar and low-polar compounds. • Higher temperatures (100-160 °C) increase polysaccharide and shogaol yields. • Above extraction temperature of 180°C, 6-gingerol was converted into 6-shogaol. • Temperatures above 180 °C harmed protein stability in the extracts.
Keywords: Ginger and Zingiberaceae research; Pharmacological Effects of Natural Compounds; Phytochemistry and biological activity of medicinal plants